Rolling horizon based multi-objective robust voltage/VAR regulation with conservation voltage reduction in high PV-penetrated distribution networks - Xu, Rui Peng; Zhang, Cuo; Xu, Yan; Dong, Zhao Yang (IET generation, transmission & distribution, 2019)
Voltage/VAR regulation (VVR) implemented by capacitor banks (CBs), on-load tap changers (OLTCs), and photovoltaic (PV)-associated inverters is effective to enhance voltage stability and reduce power loss. On the other hand, conservation voltage reduction (CVR) has been widely adopted in distribution networks to reduce load demand. Existing works mainly focus on each of them. This paper proposes a VVR method with CVR, forming a multi-objective optimisation problem which minimises (i) voltage collapse proximity indicator (VCPI), (ii) load demand, and (iii) power loss. Besides, PV power generation as uncertainty significantly impairs the VVR results. To deal with the uncertainty issue, this paper proposes a rolling-horizon framework to determine VVR and applies Taguchi's orthogonal array testing (TOAT) to model the uncertain PV power generation, achieving rolling-horizon-based multi-objective robust VVR. The proposed model is tested and demonstrated on the IEEE 33-bus and 69-bus systems, and simulation results verify that the proposed method can support robust solutions of the multi-objective VVR problem for decision-making.